Teenage Consumer Behaviour: Size and Determinants of the Teenage Mobile Phone Market in Malaysia - Eng, Jer Lin (2004)
The mobile phone services industry in Malaysia has experienced rapid expansion since the 1990s. The current mobile phone penetration rate is 47 percent of the population and this figure is expected to continue rising and reach 60 percent to 70 percent by the end of the decade (The Malay Mail, 2004; Celcom Annual Report, 2002). This indicates strong growth prospects, especially in the prepaid sector. With low mobile penetration rate for young consumers, there is extensive opportunity for this market segment to grow (Yeap, 2004). As such, teenagers have been the focus of mobile phone operators’ marketing schemes and it is imperative for mobile phone operators to identify the factors that determine the teenage mobile phone market in order to secure market leadership.The principal objective of this paper is to identify the potential size and determinants of the teenage mobile phone market in Malaysia. This research is deemed to be timely and appropriate as the findings may assist mobile phone operators effectively strategize their marketing activities targeted towards the teenage segment.A quantitative approach by means of self-administered questionnaire was used for this research. Data was collected from teenagers of age 14 years old at ten public secondary schools in Klang Valley. Four hypotheses were developed and tested using gender,mobile phone ownership, duration of ownership and income level as the bases of differentiation.This study revealed that the teenage mobile phone market is lucrative as it has high potential revenue generation. In addition, male teenagers place higher importance on functional rather than emotional benefits in their selection of mobile phone services.Teenage mobile phone owners were also found to have a higher perception of the usefulness of mobile phones and place more importance on coverage than non-owners. Similarly, old mobile phone owners have a higher perception of the usefulness of mobile phones compared to new owners. Interestingly, the income level of teenagers was not a significant predictor of the factors that determine the teenage mobile phone market.